Lens on the Texas Frontier - Jones, Lawrence T., III (Book collections on Project MUSE., 2014)
Photographs of Texas' frontier past are valuable as both art and artifact. Recording not only the lives and surroundings of days gone by, but also the artistry of those who captured the people and their times on camera, the rare images in Lens on the Texas Frontier offer a documentary record that is usually available to only a few dedicated collectors. In this book, prominent collector Lawrence T. Jones III showcases some of the most interesting and historically important glimpses of Texas history included among the five thousand photographs in the collection that bears his name at the DeGolyer.